Legal drug use patterns of adolescents in northern Hungary - Rucska, Andrea; Lakatos, Csilla (Multidiszciplinaris Tudomanyok, 2024)
In a quantitative cross-sectional study, the authors investigated the health risk behaviour of secondary school students in northern Hungary, including the consumption of legal psychoactive substances (nicotine, alcohol, caffeine). In addition to assessing substance use habits, the study should also assess mental health characteristics and examine the correlates of substance use. A total of 1251 respondents (n= 1251) took part in the survey (mean age: 16.4 years; SD: 1.6), with 59.1% of the sample being boys. The questionnaire included questions on socio-demographic data, nicotine and alcohol consumption, frequency of consumption, motivation for alcohol consumption and mental health characteristics. The results indicate that the intensity of smoking and alcohol consumption is highest in the 16-17 years old age group, with a higher prevalence of smoking among girls and alcohol consumption among boys. For smoking, lower parental education and poorer mental health are the main risk factors, and for alcohol consumption, lower parental education, a smaller settlement, poorer living conditions and poorer mental health are the main risk factors.